Merging human and machine: prosthetics anchored to bone - Joseph R. Hsu, MD; Benjamin K. Potter, MD, FACS; Danielle Melton, MD; Rachel B. Seymour, PhD (OTA International)
Abstract. Osseointegration is an emerging field that unites clinicians and researchers from a variety of disciplines. Bone-anchored transdermal prostheses (osseointegrated prostheses) have shown promising results in improving prosthetic use, mobility, quality of life, and patient satisfaction to address the challenges faced by amputees with proximal limb loss. The Global Collaborative Congress on Osseointegration (GCCO) was established to advance research and collaboration in this field. The GCCO has held annual meetings to discuss best practices, research gaps, and opportunities for clinical collaboration. The supplement includes consensus statements on key topics such as prehabilitation/rehabilitation, infection, basic science, skin and soft-tissue management, and patient selection, with the aim of providing a roadmap for addressing gaps and moving innovation forward.